Framing of Renewable Energies in Indonesian Media - Morissan (Journal of Contemporary Issues in Media & Communication (JCIMC), 2024)
Many countris are turning to renewable energies as a result of the global problem of air pollution brought on by emissions from fossil fuels. The utilization of renewable energy as a remedy for climate change problems is covered by the media but earlier studies showed ongoing controversy over media coverage of renewable energies. The purpose of this study is to determine how renewable energy is framed in the media. What kinds of renewable energy get the most attention from the media, and is there any difference in how they are framed in old and new media? Entman's framing concept—which includes "problems versus benefits," "the cause or reasons," "treatment recommendation," and "moral evaluation"—was used to conduct the quantitative content analysis. Using Google Search, articles from 2019 to 2022 were gathered. The findings indicate that there is no difference in framing between old and new media, with "problems-benefits" and "treatment recommendation" emerging as the most prevalent frames. The most frequently cited forms of renewable energies are hydropower and geothermal, and the media reports renewable energies more favorably than fossil fuels.